Solution-processed vanadium oxides as a hole-transport layer for Sb2Se3 thin-film solar cells. (1st January 2022) - Amin, Al; Guo, Liping; Vijayaraghavan, S.N.; Li, Dian; Duan, Xiaomeng; Menon, Harigovind G.; Wall, Jacob; Gupta, Subhadra; Ming-Cheng Cheng, Mark; Zheng, Yufeng; Li, Lin; Yan, Feng
Highlights: Low cost and stable solution-processed inorganic VOx hole transport layer for Sb2 Se3 solar cells for the first time. Close space sublimation deposition of a thickness of 500 nm Sb2 Se3 absorber material. Sb2 Se3 with VOx hole transport layer achieve a power conversion efficiency ∼6.3%. VOx could improve the open-circuit voltage of Sb2 Se3 solar cells. Abstract: Antimony selenide (Sb2 Se3 ) is a promising light absorber material for solar cells because of its superior photovoltaic properties. However, the current performance of the Sb2 Se3 solar cell is much lower than its theoretical value (∼32%) due to its low open-circuit voltage ( VOC ). In this paper, we have demonstrated inorganic vanadium oxides (VOx ) as a hole transport layer (HTL) for Sb2 Se3 solar cells to enhance efficiency through the VOC improvement. Here, a solution-processed VOx through the decomposition of the triisopropoxyvanadium (V) oxide is deposited on the Sb2 Se3 absorber layer prepared by close-spaced sublimation (CSS). With VOx HTL, the built-in voltage (Vbi ) is significantly increased, leading to improved VOC for the Sb2 Se3 solar cell devices. As a result, the efficiency of the device increases from an average efficiency of 5.5% to 6.3% with the VOx .